Strategy to Develop Okra (Abelmoschus esculentus L.) Plantation Based on Land Suitability Class and SWOT analysis - Andriyani, Idah; Wahyuningsih, Sri; Harsono, Soni Sisbudi; Agustina, Dwi (The University of Lampung, 2024)
Okra is famous as super food sources that prevent diabetes and reduce cholesterol. To meet the increasing demand for okra, it is necessary to develop plantation for okra cultivation. In this sense, land suitability analysis for okra plantation is needed as base information to develop the plantation development strategies. This study aimed to identify the okra plantation development strategies in Jember Regency. The strategies involved the technology recommendations needed to improve land conditions. Land suitability evaluation parameters were analyzed using ArcGIS software. The results of the analysis were used to determine internal and external factors in the SWOT (strengths, weaknesses, opportunities, and threats) analysis to determine the technology needed. Results showed that suitable area for okra plantation was divided into class S1 (highly suitable) of 56.85%, and class S2 (moderately suitable) 43.15% of the area. Moreover, based on SWOT analysis the proposed technology strategies for 7 sub districts were in the quadrant II, meaning had weaknesses. Increasing compost as fertilizer was recommended to increase N, K, and P in the soil as well as to increase soil solum. In addition, irrigation and drainage system was proposed to solve problems regarding rainfall. Recommendation to reduce sloping area included terracing development. Keywords: GIS, Land suitability analysis, Okra (Abelmoschus esculentus L.), Plantations development strategies, SWOT.